2005
DOI: 10.1182/blood.v106.11.1857.1857
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine Based Regimen (FLAI) Is an Effective Treatment for Induction of Multidrug Resistant Pgp-Positive Acute Myeloid Leukemia Patients.

Abstract: Induction treatment of acute myeloid leukemia (AML) is conventionally based on regimens containing cytarabine (Ara-C), one anthracycline and, sometimes, a third drug, such as etoposide. Primary P-glycoprotein (Pgp) overexpression is the most important mechanism of multidrug resistance (MDR) in AML cells and it is almost always associated with less response to treatment. To deal with this problem, in 1997, we started a treatment program with a regimen including Fludarabine (FLUDA) for the induction of newly dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Between 1997 and 2002, 224 newly diagnosed AML patients <65 yr were enrolled in three consecutive multicentric clinical trials (AML97, AML99 and AML02) testing the efficacy and toxicity of two fludarabine‐containing induction regimens, FLAI and FLAIE (25–27). All the enrolled patients were included in this analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Between 1997 and 2002, 224 newly diagnosed AML patients <65 yr were enrolled in three consecutive multicentric clinical trials (AML97, AML99 and AML02) testing the efficacy and toxicity of two fludarabine‐containing induction regimens, FLAI and FLAIE (25–27). All the enrolled patients were included in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The response evaluation, in terms of CR, non-responders (NRs) and death during induction (DDI) was performed according to the previously published criteria (25)(26)(27). Induction death was defined as any death before day +28 from chemotherapy start, with hypocellular marrow (25)(26)(27).…”
Section: Treatment Plansmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they suggested a probable advantage of Fluda regimens in the treatment of MDR‐Pgp‐positive (MDR‐Pgp‐pos ve ) patients that overexpressed Pgp (MFI ≥ 6 [Michieli et al , 1996a]). Indeed, it was observed that MDR‐Pgp‐negative (MDR‐Pgp‐neg ve , MFI < 6) patients and MDR‐Pgp‐pos ve patients treated with FLAI/FLAIE had a similar probability of achieving a CR, unlike what was observed with conventional regimens (Michelutti et al , 1997; Russo et al , 2005b).…”
mentioning
confidence: 99%